Downregulation of HMGA1 Mediates Autophagy and Inhibits Migration and Invasion in Bladder Cancer via miRNA-221/TP53INP1/p-ERK Axis - Liu, Xiaoqiang; Zhou, Zhengtao; Wang, Yibing; Zhu, Ke; Deng, Wen; Li, Yulei; Zhou, Xiaochen; Chen, Luyao; Li, Yu; Xie, An; Zeng, Tao; Wang, Gongxian; et al. (Frontiers in Oncology, 2020)
MicroRNAs (miRNAs) have been implicated in regulating the development and metastasis of human cancers. MiR-221 is reported to be an oncogene in multiple cancers, include bladder cancer. Deregulation of autophagy is associated with multiple human malignant cancers. Whether and how miR-221 regulates autophagy and how miR-221 been regulated in bladder cancer are poorly understood. Here, this study explored the potential functions and mechanisms of miR-221 in the autophagy and tumorigenesis of bladder cancer. We showed that downregulation of miR-221 induces autophagy via increasing TP53INP1(tumor protein p53 inducible nuclear protein 1) and inhibits migration and invasion of bladder cancer cells through suppressing activation of ERK. Furthermore, the expression of miR-221 is regulated by HMGA1(high-mobility group AT-hook1) which is overexpressed in bladder cancer. And both miR-221 and HMGA1 are correlated with poor patient survival in bladder cancer. Finally, the downregulation of HMGA1 suppressed the proliferative, migrative and invasive property of bladder cancer by inducing toxic autophagy via miR-221/TP53INP1/p-ERK axis. Collectively, our findings demonstrate that downregulation of miR-221 and HMGA1 mediates autophagy in bladder cancer and both of them are valuable therapeutic targets bladder cancer.